The Estimation of Sharia Values Connected to the Presentation of Sharia Banking - Isnaini; Ronaldo, Reza; Labetubun, Muchtar Anshary Hamid; Fahlevi, Rizal; Nguyen, Phong Thanh (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents the estimation of Sharia values connected to the presentation of Sharia banking. In respects of the wellbeing of Sharia banks, Bank Indonesia has given a Bank Indonesia Regulation (PBI) number 13/1/PBI/2011 dated January 5, 2011 concerning Assessment of Commercial Banks Health. The guideline stipulates that to gauge the presentation of Sharia banks one must utilize RGEC, which supplant CAMEL, and comprises of (1) hazard profile, (2) Good Corporate Governance, (3) Earnings, and (4) Capital. The administration intermediary utilized by CAMEL as the main subjective appraisal isn’t to be utilized any longer. The stipulation of PBI number 13/1/PBI/2011 basically didn’t bring progress however a decay. This is appeared from the estimation of Sharia banking execution which is progressively centered around parts of business direction alone. In the meantime, the qualities of Sharia banks should be as business, social and da’wah substances. Consequently, the job as social and da’wah element are at last unfit to be caught by RGEC or CAMEL execution estimation, not with standing the procedures and results that ought to be as per Sharia values that are additionally incapable to be estimated by RGEC and CAMEL.